2019
DOI: 10.3389/fmicb.2019.00082
|View full text |Cite
|
Sign up to set email alerts
|

Local Diversification of Methicillin- Resistant Staphylococcus aureus ST239 in South America After Its Rapid Worldwide Dissemination

Abstract: The global spread of specific clones of methicillin-resistant Staphylococcus aureus (MRSA) has become a major public health problem, and understanding the dynamics of geographical spread requires worldwide surveillance. Over the past 20 years, the ST239 lineage of MRSA has been recognized as an emerging clone across the globe, with detailed studies focusing on isolates from Europe and Asia. Less is known about this lineage in South America, and, particularly, Brazil where it was the pred… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
20
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(23 citation statements)
references
References 112 publications
3
20
0
Order By: Relevance
“…Our results suggest that MRSA strains with SCC mec type III form strong biofilm in glucose and NaCl supplemented TSB, whereas SCC mec type I and II strains formed strong biofilms in the presence of glucose and differed when grown in NaCl supplemented TSB. The most prevalent hospital associated (HA) MRSA lineage that carries the SCC mec type III is MRSA-ST239 [55] and recognized as multidrug resistance across the globe [56]. In the present study, we found that 28.5% ( n = 6/21) of the MRSA strains tested were of the ST239 lineage (typically referred as HA strains), and of these, the ST5-SCC mec II and ST72 lineages predominated.…”
Section: Discussionmentioning
confidence: 50%
“…Our results suggest that MRSA strains with SCC mec type III form strong biofilm in glucose and NaCl supplemented TSB, whereas SCC mec type I and II strains formed strong biofilms in the presence of glucose and differed when grown in NaCl supplemented TSB. The most prevalent hospital associated (HA) MRSA lineage that carries the SCC mec type III is MRSA-ST239 [55] and recognized as multidrug resistance across the globe [56]. In the present study, we found that 28.5% ( n = 6/21) of the MRSA strains tested were of the ST239 lineage (typically referred as HA strains), and of these, the ST5-SCC mec II and ST72 lineages predominated.…”
Section: Discussionmentioning
confidence: 50%
“…Very interestingly, despite the similar decrease in cell viability induced at 24 h by 5SA-ST5-II and 2SA-ST239-III, the latter demonstrated greater adaptability to the intracellular hostile environment, being the only one able to maintain its number during the entire period of infection. ST239 is a well-studied and widespread clone presenting some genomic characteristic features [49] as well as virulence gene content [50]. Some studies performed on bacteremic patients demonstrated the development of a non uniform and unique immune response directed to different staphylococcal proteins [51]; furthermore, a recent paper on MRSA ST239 identified a specific pattern of genes, confirming the differences among this clone and the others [52].…”
Section: Discussionmentioning
confidence: 85%
“…This clone disappeared and was replaced by the southern German clone (MRSA-ST228-I) and the New York/Japan epidemic clone (MRSA-ST5-II) between 2001 and 2004 [142]. Recent studies reported the local predominance of this clone in many countries including European countries [143,144], the Middle East, Asia, and South America [145]. Another epidemic clone, MRSA-ST22, has been predominately identified in recent years throughout the Middle East [44,45,[146][147][148][149][150][151][152][153][154], Europe [155][156][157][158][159][160], and Asia [161][162][163].…”
Section: Discussionmentioning
confidence: 99%